PENERAPAN KONSEP DIGITALISASI DALAM LAYANAN TRAVEL MOBIL UNTUK MENINGKATKAN EFISIENSI TRANSPORTASI KOTA: STUDI KASUS WOI TRAVEL - Andri Agriawan Koem; Dimas Langga Chandra; Detha Sekar Langit Wahyu G (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of applying the concept of digitalization in car travel services to improve the efficiency of city transportation. The method used in this research is Quantitative Method with data collection techniques using questionnaires distributed via GoogleForm to 86 respondents who use car travel services (Woi Travel). The results showed that the concept of digitalization affected the efficiency of city transportation by 45.9%. The remaining 54.1% is influenced by other factors not included in this study. The t test results show that the concept of digitalization has a significant effect on the efficiency of city transportation, with a tcount of 8.447 which exceeds the ttable value of 1.663. This means that the alternative hypothesis (Ha) is accepted, which shows that there is a significant effect of the application of the concept of digitalization on the efficiency of city transportation.